Src-mediated Cortactin Phosphorylation Regulates Actin Localization and Injurious Blebbing in Acinar Cells - Singh, Vijay P. (The American Society for Cell Biology, 2008)
Suprastimulation of pancreatic acini is a well-known model for pancreatitis, and it is characterized by actin reorganization and cell blebbing. Currently, however, the mechanisms underlying regulation of these aberrant cytoskeletal and membrane dynamics and how they contribute to cell injury are unclear. We observed that suprastimulation results in a rapid activation of Src and relocalization of the actin-binding protein cortactin from the apical to the basolateral domain at the necks of membrane blebs. Furthermore, Src-mediated cortactin tyrosine phosphorylation was markedly increased after suprastimulation. Pretreatment of acini with Src inhibitors or expression of a cortactin tyrosine phospho-inhibitory mutant reduced actin redistribution and bleb formation induced by suprastimulation in vitro. Importantly, inhibition of Src activity in rat models of suprastimulation-induced pancreatitis substantially reduced disease severity, as indicated by a reduction in serum amylase and pancreatic edema and a striking improvement in tissue histology. These findings indicate a novel, disease-relevant role for Src-mediated cortactin phosphorylation in aberrant reorganization of the actin cytoskeleton, a mechanism that is likely to have implications in other types of cell injury. In addition, they suggest a potential use for Src inhibitors as an approach to reduce cell injury.